Heart rate variability analysis to improve early diagnostic and prognostic differentiation of parkinsonism of uncertain etiology. A 10 years follow-up study. (14th October 2021) - Brisinda, D; Sanchioni, C; Fenici, R
Abstract: Introduction: Parkinsonian syndromes of different nature feature autonomic nervous system dysfunction (ANSd) which may herald or follow motor symptoms (MS) in Parkinson disease (PD), but anticipate by years and progress more rapidly in multiple system atrophy (MSA). Abnormal Heart Rate Variability (HRV) has been reported in both PD and MSA. Purpose: This study aimed to evaluating if HRV analysis (HRVa) could contribute to differentiate PD from MSA and to guide early and more appropriate treatment and prognostic assessment. Methods: 66 consecutive parkinsonian patients (pts) (48 males, 18 females) (mean age 63.8±10 y) were enrolled between 2010 and 2020. Initial clinical diagnosis was MSA (19), PD (20), PD with autonomic impairment (PD-AI) (10), Lewy body disease (2), supranuclear palsy (3), undefined Parkinsonism (UP) (12). The severity of MS was quantified with UPDRS and Hoehn/Yahr scales. HRV was analyzed with linear (TD and FD) and non-linear (NL) methods (Kubios Premium 3.4.1), during daily activity and NREM sleep (2-minutes intervals) and during REM sleep (1-minute Interval). 44/66 underwent also ASN functional evaluation with the Ewing protocol. Data of 52 age-matched healthy subjects (HS) were used for comparison. For statistical analysis, SPSS software (version 21) was used. Discriminant Analysis (DA) was applied to identify the more relevant parameters differentiating PD from MSA and classifying "undefined" cases. Prolonged follow-up (f-up) provided clinical diagnostic certainty, as goldstandard for validation of HRVa classification accuracy. Results: UPDRS and Hoehn/Yahr scores were higher in MSA than in PD (p<0.0001). Along 10-years of f-up, 16/66 pts died (56, 2% MSA), 5/66 had new diagnostic definition, and 15/66 were lost to f-up. Most of HRV parameters of 34 pts with certain diagnosis (17 MSA and 17 PD) whose f-up was completed, were significantly different from those of HS. VLFpower and recurrence plot parameters calculated during active wakefulness were different (p<0.05) between MSA and PD, and correctly classified them with 88, 2% predictive accuracy (PA) at DA, according to the formula: F1 = (vlfpw%ar* − 0, 087) + (rprec* − 0, 319) + (rpshen*10.81) + (−20, 53) Comparative classification accuracy of HRVa, Ewing score, UPDRS and Hoehn/Yahr scales is shown in Table 1. Attempting prognostic risk assessment by applying F1 to HRV data of pts with PD-AI and of pts with UP, those classified as MSA according to F1 showed the worst clinical outcome during the f-up. Conclusions: This study confirms that a higher degree of prevailing sympathetic ASNd in MSA compared to PD can be identified by a combination of Linear and NL HRV parameters, and correctly differentiate with high (88, 2%) predictive accuracy all pts with certain diagnosis verified during prolonged f-up. Moreover, HRVa might be useful for earlier prognostic stratification of pts with parkinsonian symptoms of uncertain nature and to improve clinical and pharmacological management. FUNDunding Acknowledgement: Type of funding sources: None.